Do Interviewers Sell Themselves Short? The Effects of Selling Orientation on Interviewers' Judgments - Marr, Jennifer Carson; Cable, Dan M. (Academy of Management Journal, 2014)
Drawing on alternative perspectives about the automaticity of dispositional judgments, we examine whether the motivation to attract the other (i.e., selling orientation) in interpersonal first meetings (e.g., job interviews) helps or hinders the accuracy and validity of dispositional judgments. In a laboratory study (Study 1), we found that selling orientation reduced the accuracy of interviewers' judgments about applicants' core self-evaluations. Then, we investigated the real-world implications of selling orientation in a field study (Study 2) with two different samples (Samples A and B) and found that a selling orientation negatively influenced the predictive validity of interviewers' judgments. Specifically, when selling orientation was low, interviewers' judgments accurately predicted which applicants would be most (and least) successful as newcomers in the organization (in terms of citizenship, performance, and fit). However, when selling orientation was high, interviewers' judgments no longer predicted applicant outcomes. Together, these results suggest that making dispositional judgments in interpersonal first meetings is an effortful process that is hindered by focusing on other goals (e.g., selling). We discuss the practical and theoretical implications of these findings.